A festival of populism: Slovakia after its 2004 presidential election - Kai-Olaf Lang (Stiftung Wissenschaft und Politik (SWP), 2004)
Ivan Gasparovic, the controversial former president of parliament, has won the presidential election in Slovakia. In the final runoff ballot on 17 April 2004, he defeated his former political associate and former prime minister, Vladimir Meciar. Both of these politicians had been largely responsible for Slovakia's international detachment during the 1990s. As Gasparovic is being supported by the most dynamic opposition power of the populist party Smer ('Direction'), the result of the election is a warning signal for Prime Minister Mikulas Dzurinda's moderate-right coalition. A new axis in Slovak politics is looming on the horizon. In addition, this election is a forewarning to the newly extended European Union (EU). The outcome of the election has shown that some populist groups and politicians have joined the EU thinking that they are capable of winning elections. The EU must decide how to deal with these members if radical, populist, and Euroskeptical parties come into power.(SWP Comments / SWP)
Keywords: 320